The Global Financial Crisis and Development Thinking - Rogers, F. Halsey (2012)
The global financial crisis has not only dealt a major blow to the global economy, but also shaken confidence in economic management in the developed world and the economic models that guide it. The crisis has revealed major market failures, especially in the housing bubble and its transmission to the financial system, but also glaring state failures that propagated and exacerbated the crisis. Will the events of the past two years lead to major shifts in thinking about development economics, and should they? This paper assesses that question for several key domains of development thinking, including the market-state balance, macroeconomic management, globalization, development financing, and public spending. On the one hand, changed global circumstances and new awareness of vulnerability should lead to some policy changes, as developing countries take steps to reduce and buffer risks, including risks generated in developed countries. At the same time, the crisis should largely reinforce the Post-Washington Consensus on development that has emerged over the past decade -- a world view that aims to achieve private sector-driven growth but sees a facilitating role for the state, promotes engaging with the global economy in ways that advance development, and values pragmatism, experimentation, and evidence-based policymaking over ideology.